The Nature of Society in the Perspective of Islamic Education Philosophy - Hasibuan, Marhan; Usiono (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The foundation of knowledge is the Philosophy of Islamic Education. Society is frequently portrayed as a group of people with similar traits and objectives. All members of society have equal rights and obligations under Islam. Islam opposes caste structures and the giving of special rights to any individual or group; in Islamic culture, a person's honor is decided only by how devoted they are to Allah. Three primary characteristics usually define an Islamic society: a focus on Allah, a high value placed on piety, and a spirit of mutual respect among its constituents. The fundamental components of an Islamic society are social justice, equality, compassion, brotherhood, and freedom. Islamic educational philosophy and society are inextricably linked, producing an inseparable synergy. As a result, Islamic.